Graph y=(6-x)/3

Math
y=6-x3
Rewrite in slope-intercept form.
Tap for more steps…
The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.
y=mx+b
Simplify 6-x3.
Tap for more steps…
Split the fraction 6-x3 into two fractions.
y=63+-x3
Simplify each term.
Tap for more steps…
Divide 6 by 3.
y=2+-x3
Move the negative in front of the fraction.
y=2-x3
y=2-x3
Reorder 2 and -x3.
y=-x3+2
y=-x3+2
Rewrite in slope-intercept form.
y=-13x+2
y=-13x+2
Use the slope-intercept form to find the slope and y-intercept.
Tap for more steps…
Find the values of m and b using the form y=mx+b.
m=-13
b=2
The slope of the line is the value of m, and the y-intercept is the value of b.
Slope: -13
y-intercept: 2
Slope: -13
y-intercept: 2
Any line can be graphed using two points. Select two x values, and plug them into the equation to find the corresponding y values.
Tap for more steps…
Choose 0 to substitute in for x to find the ordered pair.
Tap for more steps…
Replace the variable x with 0 in the expression.
f(0)=6-(0)3
Simplify the result.
Tap for more steps…
Cancel the common factor of 6-(0) and 3.
Tap for more steps…
Rewrite 6 as -1(-6).
f(0)=-1⋅-6-(0)3
Factor -1 out of -1(-6)-(0).
f(0)=-1(-6+0)3
Factor 3 out of -1(-6+0).
f(0)=3(-1(-2+0))3
Cancel the common factors.
Tap for more steps…
Factor 3 out of 3.
f(0)=3(-1(-2+0))3(1)
Cancel the common factor.
f(0)=3(-1(-2+0))3⋅1
Rewrite the expression.
f(0)=-1(-2+0)1
Divide -1(-2+0) by 1.
f(0)=-1(-2+0)
f(0)=-1(-2+0)
f(0)=-1(-2+0)
Simplify the expression.
Tap for more steps…
Rewrite -1(-2+0) as -(-2+0).
f(0)=-(-2+0)
Add -2 and 0.
f(0)=2
Multiply -1 by -2.
f(0)=2
f(0)=2
The final answer is 2.
2
2
The y value at x=0 is 2.
y=2
y=2
Choose 3 to substitute in for x to find the ordered pair.
Tap for more steps…
Replace the variable x with 3 in the expression.
f(3)=6-(3)3
Simplify the result.
Tap for more steps…
Cancel the common factor of 6-(3) and 3.
Tap for more steps…
Rewrite 6 as -1(-6).
f(3)=-1⋅-6-(3)3
Factor -1 out of -1(-6)-(3).
f(3)=-1(-6+3)3
Factor 3 out of -1(-6+3).
f(3)=3(-1(-2+1))3
Cancel the common factors.
Tap for more steps…
Factor 3 out of 3.
f(3)=3(-1(-2+1))3(1)
Cancel the common factor.
f(3)=3(-1(-2+1))3⋅1
Rewrite the expression.
f(3)=-1(-2+1)1
Divide -1(-2+1) by 1.
f(3)=-1(-2+1)
f(3)=-1(-2+1)
f(3)=-1(-2+1)
Simplify the expression.
Tap for more steps…
Rewrite -1(-2+1) as -(-2+1).
f(3)=-(-2+1)
Add -2 and 1.
f(3)=1
Multiply -1 by -1.
f(3)=1
f(3)=1
The final answer is 1.
1
1
The y value at x=3 is 1.
y=1
y=1
Create a table of the x and y values.
xy0231
xy0231
Graph the line using the slope and the y-intercept, or the points.
Slope: -13
y-intercept: 2
xy0231
Graph y=(6-x)/3

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top